Reformulation of Investigation Arrangements On Corruption In Law No. 31 of 1997 on Military Justice In Indonesia - Novalia Pertiwi; Nurini Aprilianda; Faizin Sulistyo (CV. AFDIFAL MAJU BERKAH, 2024)
This study examines the reformulation of the regulation of investigation of corruption committed by members of the military within the framework of Law No. 31 of 1997 on Military Justice. The main purpose of this study was to analyze the urgency of the KPK's involvement in the investigation of military corruption cases and to formulate a more effective reformulation of legal arrangements. This study uses the type of normative research with reference to the theory of justice, the theory of legal certainty, and the theory of Criminal Law Policy, using the approach of legislation (Statute Approach) and conceptual approach (conceptual approach). Based on the results of research conducted by the author shows that the involvement of the KPK can increase the transparency and effectiveness of law enforcement in cases of military corruption. Furthermore, because the existing military justice system has not been fully able to handle the complexity of corruption, especially due to the lack of involvement of the Corruption Eradication Commission (KPK) in the investigation process. thus, reformulation is needed to create an investigation system that is more fair, responsive, and consistent with the principle of